Assessing the Impact of Activities of the Federal Road Safety Corps in Alleviating Automobile Accidents in Minna, Niger State - Uhunwagho, Cletus; Aidelokhai, Dennis Idonije; Nmadu, Timothy; Musa , Usman; Abu, Idris (Kashere Journal of Politics and International Relations, 2025)
This study examines the Federal Road Safety Corps (FRSC) Minna Sector Command in promoting road safety and reducing road accidents in Minna, Niger State. The research focuses on evaluating the consequences of the FRSC’s initiatives, including road safety awareness campaigns, public education programs, and enforcement activities. The study reveals that the FRSC Minna Sector Command is actively engaged in conducting road safety campaigns and public education programs, which are generally perceived as effective by the respondents. The Command’s efforts in organizing awareness campaigns, public education, and regular patrols contribute positively to road safety. However, the study also identifies challenges, including inconsistent enforcement of traffic laws and inadequate resources, which impede the full effectiveness of the FRSC’s initiatives. Findings indicate that while the FRSC’s road safety campaigns and enforcement activities are appreciated, there is room for improvement in the consistency and visibility of enforcement actions. Additionally, resource constraints such as insufficient funding and personnel shortages impact the Command’s ability to fully execute its road safety programs. In conclusion, the study highlights the need for targeted improvements in the FRSC’s operations. Enhancing the regularity and visibility of enforcement activities and addressing resource limitations are critical steps toward achieving more effective road safety outcomes. The study provides valuable insights for policymakers and stakeholders in strengthening road safety measures and ensuring a safer road environment in Minna.